Podoplanin expression in salivary gland carcinomas and its clinical significance. An immunohistochemical study - Soliman, Samar; Elsherbeny, Mahmoud F; Sheta, Heba; Mohamed, Abdelaty Shawky; Fawzy, Maha M; Sakr, Doaa H.; Lotfy, Nadia (Polish Journal of Pathology, 2022)
Podoplanin (D2-40) is a lymphatic endothelial marker that is considered as a specific marker for lymphatic endothelial cells and lymphangiogenesis in salivary gland carcinomas (SGCs). Aim: the present study aimed to investigate the immunohistochemical expression of podoplanin in SGCs and to correlate its expression with the clinicopathological parameters and patients’ survival. Forty-nine SGC cases were electronically selected. Demographic, clinical, laboratory, and survival data were reviewed and tabulated. Immunohistochemistry was performed using antipodoplanin. Cases were divided into low and high expression based on a scoring system. A score of 0 and 1 was considered low expression, while > 1 was considered high expression. Podoplanin high expression was seen in 46.9% of cases, and 53.1% of cases showed low expression. Significant statistical associations were seen between podoplanin expression and tumour grade ( p ≤ 0.001), tumour-nodal- metastasis (TNM) stage (p ≤ 0.001), tumour size (p ≤ 0.001), nodal metastasis (p ≤ 0.001), tumour type (p = 0.03), prognosis (p ≤ 0.001), and mortality (p ≤ 0.001). The overall survival and progression-free survival differed significantly in cases with high and low expression (p ≤ 0.001). Podoplanin overexpression might be a significant prognostic indicator for patients with SGCs, implicating that it is a potential therapeutic target to improve survival in these cancer patients.